A study on facebook and instagram as marketing platforms for small and medium-sized businesses (SMES) among UTAR students - Kong, Si Wei (2023)
Since the internet era began, an increasing number of small and medium-sized businesses (SMEs) have started to focus on using the internet, particularly social media. It is possible to view the decision of SMEs to join social media platforms as both a strategic choice and a reaction to environmental changes. Through this action, resources and business procedures are aligned to sustain corporate performance. This paper discusses the positive impact of social media in business growth by highlighting the advantages that social media brings, and to explore the factors why small businesses prefer social media as a marketing platform on business growth. Facebook and Instagram are the two main social media platforms focused in this study. A survey with limited choice and scaled response is used to collect the data from 60 respondents.